Comparison of pollutant source tracking approaches: Heavy metals deposited on urban road surfaces as a case study. (November 2020) - Hong, Nian; Yang, Bo; Tsang, Daniel C.W.; Liu, An
Abstract: A range of source tracking approaches have been developed to identify sources in the environmental pollution research field. A comparison of source tracking approaches is essential for a better understanding and practical applications of these approaches. This study compared the commonly used source tracking approaches, namely positive matrix factorization (PMF), Unmix, flag element ratio (FER), and chemical mass-balance based stochastic approach (SCMD). A case study was illustrated for tracing heavy metals (Pb, Zn, Cr, Cu, and Ni) attached to road deposited sediments, which can significantly influence urban road stormwater quality. The results indicated that the accuracy of PMF and Unmix are affected by the number of chemical species used and whether useful markers can be identified for particular sources. However, this does not have an essential influence on FER and SCMD. PMF and Unmix are easier on data preparation and calculation processes but more difficult for source identification process than FER and SCMD. This study also provided recommendations related to the selection of source tracking approach based on different study scenarios and result requirements. These study results are able to provide important guidance for undertaking effective source tracking and devising environmental pollution mitigations. Graphical abstract: Image 1 Highlights: Four pollutant source tracking approaches (PMF, Unmix, FER and SCMD) were compared. Heavy metals attached to road deposited sediments were as a case study. FER and SCMD are easier on source identification process. PMF and Unmix are easier on data preparation and calculation. Recommendations based on study scenarios and result requirements were provided. Abstract : Four commonly used source tracking approachs were compared to provide useful guidance for undertaking effective pollutant source tracking.